2020
DOI: 10.12688/f1000research.22275.1
|View full text |Cite
|
Sign up to set email alerts
|

New developments in chondrocyte ER-stress and related diseases

Abstract: Cartilage comprises a single cell type, the chondrocyte, embedded in a highly complex extracellular matrix. Disruption to the cartilage growth plate leads to reduced bone growth and results in a clinically diverse group of conditions known as genetic skeletal diseases (GSDs). Similarly, long-term degradation of articular cartilage can lead to osteoarthritis (OA), a disease characterised by joint pain and stiffness. As professionally secreting cells, chondrocytes are particularly susceptible to endoplasmic reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Therefore, it was apparent that the lack of matrilin‐3 in the cartilage ECM in itself did not cause EDM5. In fact, later studies by Nundlall et al reported that the retention of mutant matrilin‐3 within the ER lumen induces a pathological ER stress and the UPR (Reviewed in Briggs et al 2020) 46,50 . This in turn, has detrimental consequences on chondrocyte phenotype (including decreased proliferation and increased cell death) and subsequently on endochondral ossification and long bone growth.…”
Section: Autosomal Dominant Mutations In Matrilin‐3 Cause Multiple Epmentioning
confidence: 99%
“…Therefore, it was apparent that the lack of matrilin‐3 in the cartilage ECM in itself did not cause EDM5. In fact, later studies by Nundlall et al reported that the retention of mutant matrilin‐3 within the ER lumen induces a pathological ER stress and the UPR (Reviewed in Briggs et al 2020) 46,50 . This in turn, has detrimental consequences on chondrocyte phenotype (including decreased proliferation and increased cell death) and subsequently on endochondral ossification and long bone growth.…”
Section: Autosomal Dominant Mutations In Matrilin‐3 Cause Multiple Epmentioning
confidence: 99%
“…Another group of disorders related to chondrogenesis that was studied using iPSC modelling is connected with the accumulation of proteins in the intracellular compartments of chondrocytes, leading to the activation of the unfolded protein response (UPR) [171,172,182]. Among them, we may distinguish multiple epiphyseal dysplasia (MED) and metaphyseal chondrodysplasia type Schmid (MCDS), which are related to the widening and irregularity of growth plates, an increased risk of developing early osteoarthritis of the knee and hip [171,183,184].…”
Section: Disease Modelling From Chondrogenic Ipscmentioning
confidence: 99%
“…Research on chondrodysplasias has also revealed the potential role of endoplasmic reticulum stress (ER stress) as a disease mechanism not only in the pathogenesis of rare cartilage syndromes but potentially in common OA [50]. ER stress occurs when the ability of the endoplasmic reticulum to fold proteins is defective, leading to impaired cell function and if severe enough, to cell death.…”
Section: Grebementioning
confidence: 99%